Electrotaxis-on-Chip to Quantify Neutrophil Migration Towards Electrochemical Gradients - Moarefian, Maryam; Davalos, Rafael V.; Burton, Michael D.; Jones, Caroline N. (Frontiers in Immunology, 2021)
Electric fields are generated in vivo in a variety of physiologic and pathologic settings, including wound healing and immune response to injuries to epithelial barriers (e.g. lung pneumocytes). Immune cells are known to migrate towards both chemical (chemotaxis), physical (mechanotaxis) and electric stimuli (electrotaxis). Electrotaxis is the guided migration of cells along electric fields, and has previously been reported in T-cells and cancer cells. However, there remains a need for engineering tools with high spatial and temporal resolution to quantify EF guided migration. Here we report the development of an electrotaxis-on-chip (ETOC) platform that enables the quantification of dHL-60 cell, a model neutrophil-like cell line, migration toward both electrical and chemoattractant gradients. Neutrophils are the most abundant white blood cells and set the stage for the magnitude of the immune response. Therefore, developing engineering tools to direct neutrophil migration patterns has applications in both infectious disease and inflammatory disorders. The ETOC developed in this study has embedded electrodes and four migration zones connected to a central cell-loading chamber with migration channels [10 µm X 10 µm]. This device enables both parallel and competing chemoattractant and electric fields. We use our novel ETOC platform to investigate dHL-60 cell migration in three biologically relevant conditions: 1) in a DC electric field; 2) parallel chemical gradient and electric fields; and 3) perpendicular chemical gradient and electric field. In this study we used differentiated leukemia cancer cells (dHL60 cells), an accepted model for human peripheral blood neutrophils. We first quantified effects of electric field intensities (0.4V/cm-1V/cm) on dHL-60 cell electrotaxis. Our results show optimal migration at 0.6 V/cm. In the second scenario, we tested whether it was possible to increase dHL-60 cell migration to a bacterial signal [N-formylated peptides (fMLP)] by adding a parallel electric field. Our results show that there was significant increase (6-fold increase) in dHL60 migration toward fMLP and cathode of DC electric field (0.6V/cm, n=4, p-value<0.005) vs. fMLP alone. Finally, we evaluated whether we could decrease or re-direct dHL-60 cell migration away from an inflammatory signal [leukotriene B4 (LTB4)]. The perpendicular electric field significantly decreased migration (2.9-fold decrease) of dHL60s toward LTB4vs. LTB4 alone. Our microfluidic device enabled us to quantify single-cell electrotaxis velocity (7.9 µm/min ± 3.6). The magnitude and direction of the electric field can be more precisely and quickly changed than most other guidance cues such as chemical cues in clinical investigation. A better understanding of EF guided cell migration will enable the development of new EF-based treatments to precisely direct immune cell migration for wound care, infection, and other inflammatory disorders.